Can Friendship Quality Buffer the Impact of Parental Phubbing on Adolescents’ Gratitude? The Longitudinal Mediating Role of Basic Psychological Needs’ Satisfaction - Bowen Lu; Xinyuan Shen; Xiaosong Gai; Xiaochun Xie (Behavioral Sciences)
This study aims to explore the longitudinal relationship between parental phubbing and adolescents’ gratitude, as well as the mediating role of basic psychological needs’ satisfaction and the moderating role of friendship quality. We conducted this longitudinal study in two waves with a 7-month, and surveyed 643 Chinese adolescents and constructed a moderated mediation model. The results indicated the following: First, there is a significant negative correlation between parental phubbing and adolescents’ gratitude. Second, adolescents’ basic psychological needs’ satisfaction mediates the relationship between parental phubbing and gratitude. Finally, friendship quality moderates the negative relationship between parental phubbing and adolescents’ basic psychological needs’ satisfaction and the mediating effect of basic psychological needs’ satisfaction. Specifically, compared to adolescents with lower friendship quality, the negative effect of parental phubbing on basic psychological needs’ satisfaction is stronger among adolescents with higher friendship quality, and the negative indirect effect of parental phubbing on gratitude through basic psychological needs’ satisfaction is also stronger in these adolescents. The findings suggest that parental phubbing is a significant risk factor for decreased adolescents’ gratitude, with high friendship quality adolescents being more susceptible to the impact of parental phubbing. The negative impact of parental phubbing outweighs the influence of friendship quality. This study provides insights into interventions promoting adolescents’ positive development.